Chloroplast Phylogenomic Analyses Resolve Multiple Origins of the Kengyilia Species (Poaceae: Triticeae) via Independent Polyploidization Events - Chen, Shiyong; Yan, Hao; Sha, Lina; Chen, Ning; Zhang, Haiqin; Zhou, Yonghong; Fan, Xing (Frontiers in Plant Science, 2021)
Kengyilia is a group of allohexaploid species that arose from two hybridization events followed by genome doubling of three ancestral diploid species with different genomes St, Y and P in the Triticeae. Estimating phylogenetic relationship in resolution of the maternal lineages has been difficult, owing to the extremely low rate of sequence divergence. Here, phylogenetic reconstructions based on the plastome sequences were used to explore the role of maternal progenitors in establishment of Kengyilia polyploid species. The plastome sequences of 11 Kengyilia species were analyzed together with 12 tetraploid species (PP, StP, and StY) and 33 diploid taxa representing 20 basic genomes in the Triticeae. Phylogenomic analysis and genetic divergence patterns suggested that (1) Kengyilia is closely related to Roegneria, Pseudoroegneria, Agropyron, Lophopyrum, Thinopyrum, and Dasypyrum; (2) both the StY genome Roegneria tetraploids and the PP genome Agropyron tetraploids severed as the maternal donor during the speciation of Kengyilia species; (3) the different Kengyilia species derived their StY genome from different Roegneria species. Multiple origins of species via independent polyploidization events have occurred in the genus Kengyilia, resulting in a maternal haplotype polymorphism. This helps explain the rich diversity and wide adaptation of polyploid species in the genus Kengyilia.